2009
DOI: 10.1016/j.rmed.2009.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Research in high flow therapy: Mechanisms of action

Abstract: Recently, heater/humidifier devices that use novel methods to condition breathing gases from an external source have been introduced. The addition of sufficient warmth and high levels of humidification to breathing gas has allowed for higher flow rates from nasal cannula devices to be applied to patients (i.e., high flow therapy). This article provides a review of the proposed mechanisms behind the efficacy of high flow therapy via nasal cannula, which include washout of nasopharyngeal dead space, attenuation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
531
0
21

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 659 publications
(558 citation statements)
references
References 35 publications
6
531
0
21
Order By: Relevance
“…69 Even though CPAP also uses warmed, humidified gas, an in vivo study revealed that the humidity of gas delivered by HFNC was significantly greater. 37 It is uncertain whether the increased humidity delivered by HFNC is clinically important.…”
Section: Physiologic Principlesmentioning
confidence: 99%
“…69 Even though CPAP also uses warmed, humidified gas, an in vivo study revealed that the humidity of gas delivered by HFNC was significantly greater. 37 It is uncertain whether the increased humidity delivered by HFNC is clinically important.…”
Section: Physiologic Principlesmentioning
confidence: 99%
“…9,53 Extrathoracic anatomic dead space is related to age and is higher in small infants (.3 mL/kg) compared with adults. 54 Thus, continuous washout of this relatively large space with a supply of fresh gas could be of clinical benefit, especially in the neonatal period.…”
Section: Figurementioning
confidence: 99%
“…In addition to washout of the pharyngeal dead space, decrease in inspiratory resistance, and supply of adequately warmed and humidified gas, HFNC has been shown to provide low levels of positive airway pressure, which is suspected to contribute to improving oxygenation and decreasing breathing effort. [22][23][24] Despite this physiological evidence, there are limited published studies on HFNC use in adults with ARF. Roca et al 25 were the first to show the clinical benefit of HFNC in ARF by presenting significant improvement in both clinical and physiological parameters after 30 min of HFNC compared with face-mask oxygen therapy.…”
Section: Discussionmentioning
confidence: 99%